Effect of meiotic maturation on yolk platelet lipids from Bufo arenarum oocytes - Buschiazzo, Jorgelina (2005)
Progesterone induces the resumption of meiosis in Bufo arenarum full-grown arrested oocytes through a nongenomic mechanism called meiotic maturation. Growing evidence indicates that lipids are involved in the maturation process. They are mainly located in yolk platelets, the principal organelles of amphibian oocytes. The aim of the present study was to analyze the effect of progesterone-induced maturation on lipids from B. arenarum yolk platelets. Ovarian oocytes, manually obtained, were incubated with progesterone to induce maturation. Yolk platelets were isolated by centrifugation at low velocity. Lipids were separated by thin-layer chromatography. For compositional analysis, they were derivatized by methanolysis, and were identified and quantified in a gas–liquid chromatograph. Phospholipid content decreased in progesterone-treated oocytes, mainly as a result of a decrease at the level of phosphatidylcholine (PC). The turnover of this lipid is considered crucial for the completion of meiosis. Sphingomyelin also underwent a decrease that could be related to the important role of ceramide as an inducer of germinal vesicle breakdown. Maturation effect on fatty acid composition registered significant changes in PC whose saturated fatty acids increased. A net increase in arachidonic acid was observed in phosphatidylserine after progesterone treatment. The contents of total triacylglycerols and diacylglycerols were not significantly modified by hormone effect while free fatty acids underwent a significant increase as a result of polyunsaturated fatty acids increase. Altogether, our results demonstrate that yolk platelet lipids are involved in the resumption of the meiotic cell cycle, thus suggesting that these organelles participate in a dynamic role during amphibian development